Sharing leadership for diffusion of innovation in professionalized settings. (July 2019) - Currie, Graeme; Spyridonidis, Dimitrios
Innovation often flourishes in organizational pockets, but then fails to diffuse more widely. This represents a particular global challenge in healthcare where demands of an ageing population with increasing long-term conditions need to be addressed in the face of financial constraints. Shared leadership to support diffusion of innovation may offer a panacea for the challenge. Our study shows how changing configurations of shared leadership support diffusion and adaptation of innovation. Managers remain important actors for the mandate and resourcing of innovation but, over time, powerful professionals, specifically doctors, come to the fore, to engage their peers and influence resource allocation. Nurses complement doctors' leadership efforts around engagement of frontline professionals and in adapting innovation to local context. Significant contingencies in shaping shared leadership for diffusion and adaptation of innovation are: organizational financial performance; whether nurses enact hybrid leadership roles; and whether organization is hierarchical or collaborative. Theoretically, by focusing upon leadership configuration in the process of diffusion of innovation, our study renders visible practices of shared leadership, interdependency of hierarchical managerial or professional influence, its effect upon innovation diffusion, and contingencies that underpin this.